Alterations in Ruminal Fluid and Serum Biochemical Constituents in Goats Affected with Ruminal Acidosis - Chavelikar, PR; Mandali, GC; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The Indian Journal of Veterinary Sciences & Biotechnology (2018) Volume 13, Issue 3, 6-10 ISSN (Print) : 2394-0247 : ISSN (Print and online) : 2395-1176, abbreviated as IJVSBT http://dx.doi.org/10.21887/ijvsbt.v13i3.10602 Submitted : 30-07-2017 Accepted : 15-12-2017 Published : 09-01-2018 Alterations in Ruminal Fluid and Serum Biochemical Constituents in Goats Affected with Ruminal Acidosis P.R. Chavelikar* G.C. Mandali and Neha Rao Department of Veterinary Medicine, College of Veterinary Science and Animal Husbandry, AAU, Anand-388 001 Corresponding Author: chavelikarpratik@gmail.com This work is licensed under the Creative Commons Attribution International License (http:// creativecommons.org/licenses /by/4.0/P), which permits unrestricted use, distribution and reproduction in any medium, provided the original work is properly cited. Copyright @: 2018 by authors and SVSBT. Abstract Ruminal acidosis is an important clinical emergency in small ruminants. In this study, eight healthy farm goats and 24 goats presented at TVCC of the college of Veterinary Sciences and A.H., Anand with clinical signs of ruminal acidosis and having rumen liquor pH below 6 were examined for alterations in the ruminal fluid and serum biochemical parameters. Among various rumen fluid parameters evaluated, the mean values of rumen fluid pH decreased significantly (4.71±0.11 vs. 6.90±0.10), while sediment activity time (46.67±1.20 vs. 24.50±0.78 min) and methylene blue reduction time (29.50±0.73 vs. 10.03±0.27 min) increased significantly in acidotic goats. The normal greenish, aromatic viscous color, odour and consistency of rumen fluid of healthy goats also changed to milky grey/creamy, sour/pungent watery in acidotic goats. The rumen protozoal activity decreased to nil in acidotic goats as compared to the healthy goats. Among various serum biochemical constituents, the mean values of glucose (92.43±1.37 vs. 74.13±1.83 mg/dl), BUN (26.49±0.47 vs. 22.63±1.19 mg/dl), serum creatinine (01.01±0.02 vs. 00.83±0.02 mg/dl) and albumin (03.22±0.03 vs. 03.05±0.05 g/dl), ALT (56.75±1.55 vs. 27.88±1.14 IU/L) and AST (93.25±1.82 vs. 54.00±1.75 IU/L), increased significantly, while there was significant decrease in serum calcium (09.09±0.14 vs. 10.29±0.08 mg/dl) in acidotic goats. The mean values of alkaline phosphatase (IU/L) in acidotic goats increased non-significantly from the base values of healthy goats
Keywords: Goats; Ruminal acidosis; Alterations in ruminal fluid; Serum biochemistry; Enzymatic profile.